2017
DOI: 10.1111/tpj.13571
|View full text |Cite
|
Sign up to set email alerts
|

Proteogenomic analysis reveals alternative splicing and translation as part of the abscisic acid response in Arabidopsis seedlings

Abstract: In eukaryotes, mechanisms such as alternative splicing (AS) and alternative translation initiation (ATI) contribute to organismal protein diversity. Specifically, splicing factors play crucial roles in responses to environment and development cues; however, the underlying mechanisms are not well investigated in plants. Here, we report the parallel employment of short-read RNA sequencing, single molecule long-read sequencing and proteomic identification to unravel AS isoforms and previously unannotated proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
158
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 156 publications
(167 citation statements)
references
References 86 publications
7
158
2
Order By: Relevance
“…Rice seed total RNA were ground in liquid nitrogen and extracted using a Plant RNeasy Mini Kit (Qiagen, Germany) according to the manufacturer’s instructions. RNA-sequencing (RNA-seq) experiments were conducted as previously described with minor modifications (Zhu et al, 2017). The resulting cDNA library constructed from rice seed RNA samples (Air_6 h and Hypoxia_6 h) were used for paired end (2 × 125 bp) sequencing on an Illumina HiSeq 4000 platform by Annoroad Gene Technology Co. Ltd. (Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rice seed total RNA were ground in liquid nitrogen and extracted using a Plant RNeasy Mini Kit (Qiagen, Germany) according to the manufacturer’s instructions. RNA-sequencing (RNA-seq) experiments were conducted as previously described with minor modifications (Zhu et al, 2017). The resulting cDNA library constructed from rice seed RNA samples (Air_6 h and Hypoxia_6 h) were used for paired end (2 × 125 bp) sequencing on an Illumina HiSeq 4000 platform by Annoroad Gene Technology Co. Ltd. (Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
“…The rice (Nipponbare) reference genome annotation file (Oryza_sativa.IRGSP-1.0.32) was downloaded from the Ensembl website (http://www.ensembl.org/index.html). Clean reads mapping and subsequent bioinformatic analysis was as described previously (Zhu et al, 2017). The analytical pipeline is summarized in Supplemental Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As standard RNA-seq practices are insufficient for the delineation of many mRNA isoforms, the incorporation of expressed peptide information is crucial in disambiguating this aspect of gene expression. A recent integrative study in Arabidopsis combined short-read RNA sequencing and single molecule long-read sequencing with proteomics and found that 84% of the intron-containing genes were alternatively spliced, primarily through alternative first or last exons, as detected at the RNA level [37*]. The study went further to add another dimension to the analysis: that of differential splicing in cells responding to a stimulus.…”
Section: Expanding the Annotation Of Genomesmentioning
confidence: 99%
“…In plants, this mechanism is highly induced in response to external stimuli. Recent studies reported an emerging link between splicing and ABA signalling (Zhu et al, 2017; Laloum et al, 2018). For example, the transcript encoding type 2C phosphatase HYPERSENSITIVE TO ABA 1 (HAB1), a negative regulator of ABA signalling, undergoes alternative splicing.…”
Section: Introductionmentioning
confidence: 99%